2009
DOI: 10.1098/rspb.2009.0994
|View full text |Cite
|
Sign up to set email alerts
|

Hidden levels of phylodiversity in Antarctic green algae: further evidence for the existence of glacial refugia

Abstract: Recent data revealed that metazoans such as mites and springtails have persisted in Antarctica throughout several glacial -interglacial cycles, which contradicts the existing paradigm that terrestrial life was wiped out by successive glacial events and that the current inhabitants are recent colonizers. We used molecular phylogenetic techniques to study Antarctic microchlorophyte strains isolated from lacustrine habitats from maritime and continental Antarctica. The 14 distinct chlorophycean and trebouxiophyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 58 publications
(74 reference statements)
4
125
4
3
Order By: Relevance
“…For example, Antarctic and Arctic endemites are common within diatom species complexes (Souffreau et al ., 2013; Kociolek et al ., 2017; Pinseel et al ., 2017). Antarctic microchlorophytes (De Wever et al ., 2009) or Prasiola (Moniz et al ., 2012) also possess endemic lineages. Typically, different species within a single protist genus may exhibit contrasting distribution patterns (Heesch et al ., 2016; Ryšánek et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Antarctic and Arctic endemites are common within diatom species complexes (Souffreau et al ., 2013; Kociolek et al ., 2017; Pinseel et al ., 2017). Antarctic microchlorophytes (De Wever et al ., 2009) or Prasiola (Moniz et al ., 2012) also possess endemic lineages. Typically, different species within a single protist genus may exhibit contrasting distribution patterns (Heesch et al ., 2016; Ryšánek et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Aboal & Werner, 2011;Neustupa et al, 2011). Furthermore, broad sampling of the 18S rRNA gene among various members of the class makes this marker extremely useful for identification of new, previously unknown lineages (De Wever et al, 2009;Horath & Bachofen, 2009). The rbcL gene has gradually become the standard second choice among various molecular markers in the Trebouxiophyceae and it has recently been used in several taxonomic and diversity studies (Novis et al, 2008;Thüs et al, 2011;Novis & Visnovsky, 2012), providing relatively broad sampling of individual lineages within the class.…”
Section: Discussionmentioning
confidence: 99%
“…De Wever et al (2009) reported the FJ946881 sequence from the summer phytobenthos of a lake in the Schirmacher Oasis, Antarctica. This 18S rRNA gene sequence was detected three times in a single locality, a possible indication that this alga frequently occurred in the phytobenthos of the lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this dataset and spatial modeling approaches to assess diversity patterns in Antarctica in relation to the locations of geothermal areas. Postglacial population expansion away from LGM refugia is typically marked by a distinct reduction in diversity in recolonized vs. refugial regions (36)(37)(38)(39) [including intraspecific genetic diversity (15,31,32)]. Under a hypothesis that geothermal refugia allowed persistence of Antarctic species throughout recent glacial periods, species richness is predicted to be highest close to geothermally active areas and lower in nonactive regions, with significant nestedness (40) of taxa from high-to low-richness areas, consistent with postglacial recolonization of more distant sites by a subset of the refugial taxa.…”
Section: Significancementioning
confidence: 99%